Candidature file of the Mevlevi Sema Ceremony : known historically as the Mevlevi Âyîn-i Şerîf or Sema Mukabele-i Şerîf the Mevlevi sacred rituals or sacred encounter of whirling for UNESCO’s proclamation of “masterpieces of the oral and intangible heritage of humanity : tables, notations & lyrics (güftes) (Ankara)
yak 300 s.